ANALYZING THE OUTCOMES OF THE SIX-WEEK TRAINING PROGRAM ON FOOTBALL PLAYERS - Dar, Sajid Yousaf; Singh, Amarjeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the effects of a six-week structured training program on football players, specifically targeting improvements in shooting and dribbling skills. The training was designed to enhance overall match performance by incorporating focused physical and technical drills. To evaluate the program's effectiveness, pre- and post-intervention tests were conducted, with two null hypotheses proposing that the training would not lead to significant improvements in performance. The analysis revealed notable enhancements in both shooting and dribbling abilities, demonstrating that even short-duration; sport-specific training can significantly impact player development. The study underscores the value of structured training routines in football and advocates for the integration of physical education strategies in athletic training programs.